2011
DOI: 10.1242/dev.057687
|View full text |Cite
|
Sign up to set email alerts
|

DPP-mediated TGFβ signaling regulates juvenile hormone biosynthesis by activating the expression of juvenile hormone acid methyltransferase

Abstract: SUMMARYJuvenile hormone (JH) biosynthesis in the corpus allatum (CA) is regulated by neuropeptides and neurotransmitters produced in the brain. However, little is known about how these neural signals induce changes in JH biosynthesis. Here, we report a novel function of TGF signaling in transferring brain signals into transcriptional changes of JH acid methyltransferase (jhamt), a key regulatory enzyme of JH biosynthesis. A Drosophila genetic screen identified that Tkv and Mad are required for JH-mediated sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 41 publications
6
79
1
1
Order By: Relevance
“…The overexpression of Z1-3 caused AMPs and PCs to prematurely differentiate into Pdm1-positive EC-like cells, whereas overexpression of Z4 did not affect the timing of AMP/PC differentiation. These results are consistent with a recent report that found that only the Z1-3 isoforms are expressed in larvae (Huang et al, 2011). We only showed data of overexpressing br Z3 in the text.…”
Section: Fly Strainssupporting
confidence: 93%
See 1 more Smart Citation
“…The overexpression of Z1-3 caused AMPs and PCs to prematurely differentiate into Pdm1-positive EC-like cells, whereas overexpression of Z4 did not affect the timing of AMP/PC differentiation. These results are consistent with a recent report that found that only the Z1-3 isoforms are expressed in larvae (Huang et al, 2011). We only showed data of overexpressing br Z3 in the text.…”
Section: Fly Strainssupporting
confidence: 93%
“…Although the detailed molecular mechanisms of JH and 20E action remain elusive, accumulated evidence suggests that their effects converge on a key transcriptional regulator, Broad (Br, also called BroadComplex or BR-C). The expression of br is directly induced by 20E but inhibited by JH (Huang et al, 2011;Konopova and Jindra, 2008;Suzuki et al, 2008;Zhou et al, 1998;Zhou and Riddiford, 2002). Flies with a loss-of-function br mutation develop normally to the end of L3, but they do not enter the pupal stage (Kiss et al, 1988;Restifo and White, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster (Dm), it was reported that loss of Dm'mad, Dm'tkv, or Dm'dpp caused precocious metamorphosis, even in the early larval stages (20). Therefore, we first examined whether Dpp signaling plays a role in regulating Gryllus metamorphosis.…”
Section: Resultsmentioning
confidence: 99%
“…JH-mediated repression of the activation of BR-C by 20E has been also reported in cultured insect epidermis, but the inhibitory effect of JH declined after the transition to the pupal commitment phase (30,35). A study using the Kr-h1 mutant of Drosophila melanogaster showed that Kr-h1 was required for the repression of BR-C expression in the fat body of young D. melanogaster larvae (36); however, the molecular mechanism underlying the JH-mediated repression of BR-C, particularly whether the BR-C expression is directly repressed by Kr-h1 or repressed by Kr-h1-inducible gene(s), has remained unclear.…”
mentioning
confidence: 77%